Readiness to Purchase Airline Tickets through Smartphone: A Malaysian Perspective - Philips, Remo (2013)
Increased popularity in using new technology made Companies to invest hugely to bring up new technologies in smartphones. The breakthroughs of internet into the society, people are more advanced in wireless and networking. There has been a high increase in the internet users and people who stays online always. Most of them are always using their smartphone for internet purpose and stay online every time. Another sudden change in consumer’s life was online purchasing, now a days consumers purchase many things online which includes books to groceries. But question remain unanswered regarding the consumers perception towards accepting a new technology like purchasing through their smartphone. So the research is to find out the consumers perception in purchasing airline tickets through their smartphone. Unfortunately, there are no quantitative studies done to find consumers readiness to purchase airline tickets through smartphones which is a common and high purchasable item. Throughout the study it concentrates more on the various aspects of technological readiness and intention of the consumers to purchase online. The study will be conducted in the urban areas of Kuala Lumpur and Selangor, which are considered to be the highly populated areas of Malaysia. Quantitative research approach is used in the study to get more details from the respondents. A well-drafted survey will be distributed in the particular locations of the study. The sample sizes of the study are considered to be 400 because of time limit of the study. Out of the 400 questionnaire, 333 were effective and usable. Reliability analysis was done to check reliability and validity of the variables. Regression was used to check the relationship between the independent and dependent variables. The finding of this study indicates that there is a significant association between Optimism, Innovativeness whereas Insecurity and Discomfort showed inverse relationship with intention to purchase through smartphone.